2013
DOI: 10.1093/jxb/ert079
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative high resolution mapping of HvMLH3 foci in barley pachytene nuclei reveals a strong distal bias and weak interference

Abstract: In barley (Hordeum vulgare L.), chiasmata (the physical sites of genetic crossovers) are skewed towards the distal ends of chromosomes, effectively consigning a large proportion of genes to recombination coldspots. This has the effect of limiting potential genetic variability, and of reducing the efficiency of map-based cloning and breeding approaches for this crop. Shifting the sites of recombination to more proximal chromosome regions by forward and reverse genetic means may be profitable in terms of realizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 78 publications
3
42
1
Order By: Relevance
“…Barley meiocytes at pachytene were embedded in acrylamide in order to preserve their three‐dimensional architecture, exactly as described in Phillips et al . (). The subsequent immunolocalisation and FISH procedure, including probe labelling conditions, were performed as described in Phillips et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Barley meiocytes at pachytene were embedded in acrylamide in order to preserve their three‐dimensional architecture, exactly as described in Phillips et al . (). The subsequent immunolocalisation and FISH procedure, including probe labelling conditions, were performed as described in Phillips et al .…”
Section: Methodsmentioning
confidence: 97%
“…Genetic background in barley has been shown to influence CO frequency in both cytological studies (Gale & Rees, ; Phillips et al ., ) and genetic mapping (Bengtsson & Säll, ; Säll, ). Differences in genetic background (together with environmental effects) potentially contribute to the differences in genetic map length found in more recent genome‐wide mapping studies though the general distal distribution of recombination is maintained (Close et al ., ; Mayer et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In barley, it marks late recombination nodules, the future sites of interference-dependent COs (Phillips et al, 2013). The number of MLH3 foci during prophase I in the empty vector control line (15 6 2.4, n = 10) was significantly greater (P < 0.001, 51 df) than the number of pooled MLH3 foci from the ZYP1 RNAi lines (2 6 0.2, n = 42) (Figures 7E and 7J; Supplemental Figure 10 and Supplemental Table 2).…”
Section: Dsb Formation Appears Normal But the Recombination Pathway Imentioning
confidence: 99%
“…Immunolocalization and other cytological techniques were performed according to Higgins (2013). Antibodies were used at a concentration of 1:200 including At-ASY1 rat, At-ZYP1 rat, gH2AX rabbit (Millipore), At-RAD51 rabbit, At-MSH4 rabbit, and Hv-MLH3 rabbit (Phillips et al, 2013). For the cytological time course, 10 mM BrdU (0.5 mL) was injected into barley influorescences, which were then fixed in 3:1 ethanol:acetic acid at various time points and detected with BrdU labeling and detection kit I (Roche Diagnostics), as in Higgins (2013).…”
Section: Cytological Proceduresmentioning
confidence: 99%
“…Immunolocalization of MLH3 foci along barley chromosomes at pachytene has revealed that the mean inter-focus distances range from 29.2% to 44.35% of arm length for chromosomes 2H and 3H, with a minimum distance of 6.1% (83). Overall, nearly 40% of the MLH3 foci were separated by less than 20% of arm length.…”
Section: Effect Of Temperature On Meiotic Recombinationmentioning
confidence: 99%